Exercise, But Not Acute Sleep Loss, Increases Salivary Antimicrobial Protein Secretion. Issue 5 (May 2015) - Gillum, Trevor L.; Kuennen, Matthew R.; Castillo, Micaela N.; Williams, Nicole L.; Jordan-Patterson, Alex T.
Abstract : Abstract: Gillum, TL, Kuennen, MR, Castillo, MN, Williams, NL, and Jordan-Patterson, AT. Exercise, but not acute sleep loss, increases salivary antimicrobial protein secretion. J Strength Cond Res 29(5): 1359–1366, 2015—Sleep deficiencies may play a role in depressing immune parameters. Little is known about the impact of exercise after sleep deprivation on mucosal immunity. The purpose of this study was to quantify salivary antimicrobial proteins (AMPs) in response to sleep loss before and after exercise. Four men and 4 women (age: 22.8 ± 2; : 49.1 ± 7.1 ml·kg −1 ·min −1 ) completed 2 exercise trials consisting of 45 minutes of running at 75% after a normal night of sleep (CON) and after a night without sleep (WS). Exercise trials were separated by 10 ± 3 days. Saliva was collected before, immediately after, and 1 hour after exercise. LL-37, HNP1-3, Lactoferrin (Lac), and Lysozyme (Lys) were measured. Sleep loss did not affect the concentration or secretion rate of AMPs before or in response to exercise. However, exercise increased the concentration from pre- to post-exercise of LL-37 (pre: 15.5 ± 8.7; post: 22.3 ± 16.2 ng·ml −1 ), HNP1-3 (pre: 2.2 ± 2.3; post: 3.3 ± 2.5 μg·ml −1 ), Lac (pre: 5, 234 ± 4, 202; post: 12, 283 ± 10, 995 ng·ml −1 ), and Lys (pre: 5, 831 ± 4, 465; post: 12, 542 ± 10, 755 ng·ml −1 ), p ⩽ 0.05. The secretion rates were higher immediately after and 1 hour after exercise compared with before exercise for LL-37 (pre: 3.1 ± 2.1; post: 5.1 ± 3.7; +1: 6.9 ± 8.4 ng·min −1 ), HNP1-3 (pre: 0.38 ± 0.38; post: 0.80 ± 0.75; +1: 0.84 ± 0.67 μg·min −1 ), Lac (pre: 1, 096 ± 829; post: 2, 948 ± 2, 923; +1: 2, 464 ± 3, 785 ng·min −1 ), and Lys (pre: 1, 534 ± 1, 790; post: 3, 042 ± 2, 773; +1: 1, 916 ± 1, 682 ng·min −1 ), p ⩽ 0.05. These data suggest that the major constituents of the mucosal immune system are unaffected by acute sleep loss and by exercise after acute sleep loss. Exercise increased the concentration and secretion rate of each AMP suggesting enhanced immunity and control of inflammation, despite limited sleep.